Leadership Behaviors and Organizational Commitment in Nepali Public Enterprises: A Qualitative Exploration - Khanal, Shrimani Raj; Sharma, Ravi (A Bi-annual South Asian Journal of Research & Innovation, 2024)
This research paper examines the complex relationship between leadership behaviors and organizational commitment within the context of Nepali public enterprises. It has used a qualitative research approach in phenomenology. The study identifies the prevalent leadership behaviors exhibited by managers. It has focused on their frequency, intensity, and effectiveness in development of employee engagement and motivation. Transformational leadership, characterized by inspiration, motivation, and individualized consideration, emerges as a critical driver of organizational commitment. In contrast, transactional leadership is found to be effective in achieving short-term goals but less impactful in cultivating long-term commitment. The study also explores the factors influencing organizational commitment, such as job satisfaction, organizational culture, perceived fairness, and trust in leadership. These factors have a vital role in influencing employees’ emotional attachment, perceived costs of leaving, and sense of obligation within Nepali public enterprises. The findings enhance the understanding of how leadership behaviors impact organizational commitment in Nepali public sector. It provides practical recommendations for leaders in Nepali public enterprises, emphasizing the need for context specific strategies that address the challenges of the public sector for reform and modernization to enhance employee commitment and organizational success.